2018
DOI: 10.1097/ccm.0000000000002813
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Inhibition of Tumor Necrosis Factor Receptor 1 and Matrix Metalloproteinase 8 Completely Protects Against Acute Inflammation and Sepsis

Abstract: Inhibition of matrix metalloproteinase 8 and tumor necrosis factor receptor 1 might have therapeutic potential to treat sepsis and proof-of-principle was provided as therapeutics that inhibit both tumor necrosis factor receptor 1 and matrix metalloproteinase 8 are effective in CLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 46 publications
3
15
1
Order By: Relevance
“…In contrast to our observations [67], Ebach et al reported that TNFR1 KO mice had prolonged survival in CLP and they found that TNFR2 KO mice were more sensitive and had more severe hypothermia than WT mice [75]. When polymicrobial sepsis was initiated by i.p.…”
Section: Differential Roles For Tnfr1 and Tnfr2 In Sepsiscontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to our observations [67], Ebach et al reported that TNFR1 KO mice had prolonged survival in CLP and they found that TNFR2 KO mice were more sensitive and had more severe hypothermia than WT mice [75]. When polymicrobial sepsis was initiated by i.p.…”
Section: Differential Roles For Tnfr1 and Tnfr2 In Sepsiscontrasting
confidence: 99%
“…Interestingly, TNFR1 -/-mice also experienced less sepsis-induced memory deficits, possibly by increased hippocampal expression of BDNF [71]. However, despite of these interesting observations, TNFR1 KO mice were not protected against very high LPS doses [39,63], which of 59 our lab also confirmed in previous research [67]. The previous models are sterile models, and observations in CLP, which is considered as the golden standard for human polymicrobial sepsis [72], or in colon ascendens stent peritonitis (CASP) left the scientific community with contradictory results regarding the different roles of TNFR1 and TNFR2 in real sepsis models.…”
Section: Differential Roles For Tnfr1 and Tnfr2 In Sepsissupporting
confidence: 79%
See 2 more Smart Citations
“…7,8 Inhibition of the production of proinflammatory cytokines is a promising approach for the treatment of sepsis. 9 Recent studies on the pathogenesis of sepsis revealed the participation of noncoding RNAs, such as microRNAs and long (>200 nt) noncoding RNAs (lncRNAs). 10,11 For instance, miR-27a upregulates the gene encoding TNF-a (TNFA) to relieve the inflammation of sepsis.…”
Section: Introductionmentioning
confidence: 99%